Leonardo s Representational Technique for Centrally-Planned Temples - João Pedro Xavier (2008)
The aim of this paper is to verify how Leonardo's invention of a new representational technique for centrally planned temples - combining as a system, the building plan and a bird's eye perspective - is related to his own architectonic research on centralized space. In general it is proved the mutual dependence of this kind of representation and form result, but for some cases, it is also detected some limitations of the system, as is the case of the squared plan temple presented in MS 2037, fol. 3v, to which is proposed, according to Leonardo's clues and a few contemporary architectonic examples, some hypothesis for the whole shape of the building.